Synthesis of Some New Chalcone Compounds Derived From (Phenyl Quinoxaline Methyl Benzotriazol) of an Expected Biological Activity - Natiq Ahmed; Hussein Ridha (College of Education for Pure Sciences, 1970)
This study include the synthesis of the compound 2,3-Diphenyl quinoxaline from (the reaction of ortho Phenylenediamine with Benzil) and then connect this molecule with benzotriazole molecule, using the Methylene bridge through using formaldehyde in acidic medium to obtain the compound 6-[(1H-Benzotriazol-5-yl)methyl]-2,3-diphenylquinoxaline which having acidic hydrogen at the nitrogen atom which could be reacted with chloroacetone to form ketonic compound (2), that can be react with different aromatic aldehydes (4-nitrobenzaldehyde and 4-methoxy benzaldehyde) or 4-nitro acetophenone through aldol condensation to obtain an α,-unsaturated carbonyl compounds (single chalcones) (3-6), from which we could prepare a double chalcones (7-11), these compounds are used to prepare many heterocyclic compounds as derivatives, when reacted with hydrogen peroxide gave oxirane compounds (a ring with three atoms) (12-16), with bromine in the presence of a base, gives mono substituted bromine (17-21),with hydrazine hydrate and phenyl hydrazine gave the pyrazoline compounds and their substituted compounds (a ring with five atoms) (22-31) and finally with hydroxyl amine hydrochloride to give the isooxazoline compounds (32-36). The synthesized compounds were identified using physical and spectral methods (melting points, colour change, infrared spectra, ultraviolet spectra, nuclear magnetic resonance spectra), also bromine test were used to the detection of the double bond which present on the single and double chalcones.